Analisis Pengadaan Tempat Sampah dalam Meningkatkan Kesadaran Kebersihan di Lingkungan Kelas V Madrasah Ibtidaiyah Ma’had Al-Zaytun - Dinda Mardianah; Dewi Utami; Dede Indra Setiabudi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This article examines the use of trash bins in raising awareness of cleanliness among students taking environmental conservation courses. Awareness of cleanliness is the ability of a person to understand environmental cleanliness. Some students are still unaware, lack discipline in disposing of trash, and there is no trash bin sorting in the environment. The main issue in this study is to determine the implementation of trash bin provision in improving hygiene awareness in the 5th-grade class environment. The research method used is a qualitative approach with in-depth interviews and observations of students, 5th-grade teachers at MI Ma’had Al-Zaytun, and the school principal. The research subjects consist of 4 students, 2 teachers from the 5th grade at MI Ma’had Al-Zaytun, and 1 school principal. The data collection techniques used by the researcher are in-depth interviews and observations of students, 5th-grade teachers at MI Ma’had Al-Zaytun, and the school principal. The research subjects consist of 4 students, 2 teachers Al-Zaytun, and the school principal. The research subjects consisted of 4 students, 2 fifth-grade teachers at MI Ma’had Al-Zaytun, and 1 school principal. The data collection techniques used by the researcher were interviews, observations, and documentary studies. The data analysis stages conducted by the researcher were data reduction, data display, and conclusion drawing. The research results showed that hygiene awareness in the fifth-grade environment at The research results indicate that hygiene awareness in the 5th grade environment of Madrasah Ibtidaiyah Ma’had Al-Zaytun already has good hygiene awareness, supported by the existence of a hygiene duty schedule,a reward system, as well as the role of teachers and the school principal in guidance and supervision. This study found that students understand the importance of maintaining cleanliness. Cleanliness evaluations are conducted regularly. Discipline challenges are addressed through habit formation and character development to foster environmental responsibility.